Antibacterial action of the urease inhibitor acetohydroxamic acid on Helicobacter pylori. Issue 4 (April 1993) - Phillips, K; Munster, D J; Allardyce, R A; Bagshaw, P F
Abstract : The urease inhibitor acetohydroxamic acid (AHA) was assessed for its bacteriostatic and bactericidal effects on Helicobacter pylori. For eight isolates of H pylori, the minimum inhibitory concentration (MIC) was either 200 mg/l or 400 mg/l. Interactions between AHA and antimicrobial drugs used to treat H pylori were also determined. For most isolates AHA reduced the MIC for colloidal bismuth subcitrate (CBS), tetracycline, metronidazole, and amoxicillin. In a few isolates, however, AHA increased the minimum bactericidal concentration (MBC) for these antimicrobial treatments. In vitro AHA is active against H pylori and it interacts with other agents directed against H pylori.